Onward and Upward: Affording a Future - Byron Mouton (Oz, 2006)
I have lived in New Orleans all my life; the only exception being six years of study in the Northeast and abroad. A descendant of a large family with more than a century of heritage in the region, I am ingrained in a local condition where generation upon generation is rooted in the same place—a circumstance unfamiliar to most Americans, and many American cities. Ed. note: Byron Mouton with Cordula Roser and Julie Charvat.